Strategy-specific decision making : a guide for executing competitive strategy - Forgang, William G., 1946- (M.E. Sharpe, 2004)
Providing a novel approach to business policy and strategic management, this book focuses on the implementation of a firm's competitive strategy throughout all levels of the organization.